The Dynamics of Study-Work Choice and Its Effect on Intended and Actual University Attainment - Xiaodong Gong (Institute of Labor Economics (IZA), 2017)
We study the dynamics of study-work choices of Australian high school students and how these choices affect intended and actual enrolment in universities when they finish their school education. A dynamic random effect multi-equation model is constructed and estimated. We find that study-work choices are state dependent, driven by student heterogeneity and the school environment they are in. They are also related to behaviours of the fellow students in the same school. We find that study-work choices significantly affect enrolment in universities but they hardly have any effect on students' preference for university attainment.
Keywords: I21; C33; 330; study-work choices; university enrolment; dynamic models